Pengaruh Store Atmosphere dan Lokasi Terhadap Keputusan Pembelian Konsumen Pada Toko Zam-Zam Kota Bima - Feni Farizal; Muhajirin Muhajirin (Forum Kerjasama Pendidikan Tinggi, 2020)
This study aims to determine the effect of store atmosphere and location on consumer purchasing decisions in zam-zam stores in Bima City. The population in this study are consumers who have made a purchase. The sample used in this study amounted to 120 people. This type of research is an associative study using random sampling techniques (random sampling) which is carried out using validity and reliability tests to determine the attributes that have data validity. In the first description that has been done, it proves that the indicators used are correct to assess the existing variables. The next form shows that Store atmosphere affects consumer purchasing decisions at zam-zam stores in Bima City, Location affects consumer purchasing decisions at zam-zam stores in Bima City, Store atmosphere and location simultaneously influence consumer purchasing decisions at zam-zam stores in Kota. Bima